Effect of Market Share and Firm Size on Efficiency and its Implications to Profitability of Sharia Insurance in Indonesia - Said Aryonindito; Winwin Yadiati; Sofik Handoyo (Journal of Accounting Auditing and Business, 2020)
Since Indonesia as a developing country which consists of 87.2% of Muslim citizens, sharia insurance plays an important role. However, this presence of sharia insurance does not show significant growth compared to Malaysia. This study aims to determine whether efficiency may serve as an intermediary variable in linking market share and company size to the profitability of Islamic insurance in Indonesia. It employs secondary data to collect data by involving 11 sharia insurance companies with 4 years ranging from the year 2014 to 2017. The collected data were analyzed through Path analysis and Sobel test with the DEA VRS as an indicator of efficiency. In analyzing the collected data, the Path equation has passed the classic assumption test. The findings reveal that the market share and company size have respectively significant positive and negative influences on efficiency. It indicates that market share is a variable that shows a significant positive effect on profitability compared to the other two variables. Whereas, the results of Sobel tests show that efficiency cannot serve as an intermediary in this research model